2019
DOI: 10.12998/wjcc.v7.i11.1291
|View full text |Cite
|
Sign up to set email alerts
|

Application of pulse index continuous cardiac output system in elderly patients with acute myocardial infarction complicated by cardiogenic shock: A prospective randomized study

Abstract: BACKGROUND Cardiogenic shock (CS) secondary to acute myocardial infarction (AMI) complicates management of the condition, and often leads to poor prognosis. Prompt and accurate monitoring of cardiovascular and accompanying hemodynamic changes is crucial in achieving adequate management of the condition. Advances in technology has availed procedures such as pulse index continuous cardiac output (PiCCO), which can offer precise monitoring of cardiovascular functions and hemodynamic parameters. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…This clinical study is the first real-world prospective observational study to investigate the safety and efficacy of early PiCCO monitoring in elderly patients with coronary heart disease and severe heart failure. The results showed that invasive PiCCO monitoring reduced the risk of hospital/CCU stay without increasing the incidence of 1-month mortality, which is consistent with other reports ( 11 , 12 ). PiCCO indicators reflect cardiac function in order to precisely and accurately diagnose, treat, and prevent.…”
Section: Discussionsupporting
confidence: 92%
“…This clinical study is the first real-world prospective observational study to investigate the safety and efficacy of early PiCCO monitoring in elderly patients with coronary heart disease and severe heart failure. The results showed that invasive PiCCO monitoring reduced the risk of hospital/CCU stay without increasing the incidence of 1-month mortality, which is consistent with other reports ( 11 , 12 ). PiCCO indicators reflect cardiac function in order to precisely and accurately diagnose, treat, and prevent.…”
Section: Discussionsupporting
confidence: 92%
“…31,32 The PiCCO™-guided hemodynamic management shortened the duration of vasoactive therapy, mechanical ventilation and ICU stay among elderly patients with cardiogenic shock after acute myocardial infarction. 33 However, there is a lack of evidence regarding the effect of PiCCO™ monitoring system and PiCCO™ guided therapy on mortality in post-cardiac arrest treatment -and this is why our study ndings are unique and much needed.…”
Section: Discussionmentioning
confidence: 98%
“…Identification of patients who will not benefit from fluid therapy avoids harmful fluid overload, and after hemodynamic stabilization it enables the controlled correction of the cumulative positive balance with the use of diuretics and continuous renal replacement therapies [21]. Contrary to thermodilution, the CS application, based on the APCO method, does not provide several useful parameters, such as the extravascular lung water index (EVLWI), the intrathoracic blood volume index (ITBVI), and the global end-diastolic volume index (GEDVI) [22]. However, in the absence of thermodilution methods, repeated SV and/or PPV assessment in the CS application during the fluid challenge or passive test raising (PLR) may be a valuable supplement to the assessment of fluid susceptibility [23].…”
Section: Discussionmentioning
confidence: 99%